PELATIHAN PENGGUNAAN SISTEM MONITORING KUALITAS AIR KOLAM DI DINAS PERIKANAN OGAN KOMERING ILIR SUMATERA SELATAN - Abdul Rahman; Dedy Hermanto; Mulyati Mulyati; Inayatulah Inayatulah (FORDICATE, 2026)
Inefficient water monitoring remains a challenge for aquaculture in Ogan Komering Ilir. This community service initiative aims to equip local Fishery Service staff with the skills to operate digital water quality monitoring systems. Using socialization, tool demonstrations, and hands-on practice, participants were trained to accurately monitor crucial parameters such as pH, temperature, and oxygen levels. The results indicate a strengthening of technical capacity in adopting sensory systems for pond oversight. By transitioning from manual to digital methods, staff can now detect water quality degradation early to prevent farmer losses. This program is expected to drive the modernization of the fishery sector in South Sumatra by optimizing the supervisory functions of the relevant agency.